A modified rain attenuation prediction model for tropical V-band satellite earth link - Badron, Khairayu; Ismail, Ahmad Fadzil; Islam, Md. Rafiqul; Abdullah, Khaizuran; Din, Jafri; Tharek , Abdul Rahman (John Wiley & Sons, Ltd, 2014)
Radio wave propagation plays a very important part in the design and eventually dictates performance of space communication systems. Over time, the requirements of satellite communication have grown extensively where higher capacity communications systems are needed. Escalating demands of microwave and millimetre wave communications are causing frequency spectrum congestion. Hence, existing and future satellite system operators are planning to employ frequency bands well above 10 GHz. The challenge in operating at such high frequencies for communication purposes is that there exists stronger electromagnetic interaction between the radio signals and atmospheric hydrometeors. Such instances will degrade the performance of such high frequency satellite communication systems. The development of a revised model for a better-improved rain fade prediction of signal propagations in tropical region is considered very important. Researchers and engineers can employ the model to accurately plan the future high frequencies satellite services.